Temperature-dependent pressure-induced softening in Zn(CN)(2) - Fang, H; Phillips, A; Dove, M; Tucker, MG; Goodwin, A (2013)
We study the temperature dependence of the pressure-induced softening in the negative thermal expansion material Zn(CN)2 using neutron powder diffraction and molecular dynamics simulations. Both the simulation and experiment show that the pressure-induced softening only occurs above a minimum temperature and also weakens at high temperatures. © 2013 American Physical Society.